The Application of E-Learning Model with Quipper School Media to Improve Learning Outcomes - Ahmad Faesol Qorib; Tri Susilaningtyas; Sholahudin Al Ayubi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to improve student learning outcomes by applying the e-learning model using the quipper school. This research uses classroom research. The subject of this research is the VIII grade students at MTs. Nurul Ulum. Many students, there are 20 people as recipients of the action and the researchers use data collection methods in the from of interview, observations, and tests. The result of this study can be seen from the indicators of the success of the cycle, in cycle I it can be seen  that student learning outcomes get 60% then in cycle II 85%. From these indicators of success, it is concluded that the application of the e-learning model using the quipper school application on student learning outcomes has increased   Keywords: e-learning, quipper school, learning outcomes